Assessing effective properties of continuous carbon fiber-reinforced composites with the preset cracks. Issue 21 (20th October 2021) - Xi, Jiale; Ye, Junjie; Hong, Yun; An, Ningli; Shi, Yang; Cai, Gaigai; Wang, Yongkun; He, Yumin
Abstract: Initial microscopic damages, fiber fracture, and matrix cracking, usually occur in composites during their fabrication and secondary processing. Evaluating these initial damages influence on the mechanical properties of composites has a great importance for their optimal design. To this end, a parametric microscopic model with preset cracks was proposed in this article. The effectiveness of the method was assessed by comparing of the local stress distributions and effective modulus with other numerical methods. To describe nonlinear deformations of resin matrix, a viscoplastic constitutive model was introduced. On this basis, the relationships between the crack evolution and the microscopic stress field are discussed in details. It was revealed that the maximum stress at the crack tip presents different variations with the crack evolution in fiber or matrix materials.